The success model of evolution from government to e-governance - Perumal, Sundresan; Rajarethinam, Premma; Jamaludin, Zulikha (Global Institute of Flexible Systems Management (GIFT) Publishing, 2006)
As the world is streaming into the electronic world there are still huge communities which don’t understand the revolution of government which already switch into the era of e-government.There are still a huge community which till now does not understand what is actually e-government and e –governance. And at the same time they don’t understand what is actually the transmission between the old government and the new e government framework model. The actual positive idea to develop this model is to understand the e-governance better and at the same time this will avoid from possible problem during the period of transition. Towards introducing the new model we also will identify new model we also will identify few unique cases of e-government. As fast as WWW (World Wide Web) concern it grows beyond the limitation line, this made a considerable attention to be focused on the adoption of web-based technology to the business to business (B2B) and business to consumer (B2C) sector. As the heat of this sector goes on another few are also entering into the picture whereby involving government such as government to business (G2B) and government to citizen (G2C) this wont be a shocking if the government whether local, regional, national, or even supranational have been slower to clamber onto the web enabled bandwagon. The concepts of the traditional government are more conservative entity,slower to change into new initiatives, than operators in the commercial fields.